Praktik Periklanan Online Terhadap Testimoni Produk Pelangsing Dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen dan Etika Bisnis (Studi Kasus Terhadap Produk Pelangsing Hindi 7 Days dan Joyjus Fiber pada Aplikasi Instagram) - Meirza Aulia Chairani; Trinah Asi Islami (Universitas Merdeka Madiun, 2021)
Online trading in the industrial era 4.0 is a trading method that is very popular with consumers. In addition to an easy, fast and practical process, of course online trading also has several weaknesses, including manipulation of advertising, which in fact the image contained in the advertisement does not match the real product. This is often found by consumers who use e-commerce trading systems. One of them is in the case of testimonials of Hindi 7 days slimming products and Joyjus Fiber which advertises their products through social media in the form of the Instagram application, where the two products upload testimonials with images and words in the same advertisement even though the two products are different business actors. The method used in this research is legal research using a statutory approach, conceptual approach and case studies taken from real cases on Hindi 7 days slimming products and Joyjus Fiber. Related to the type of research used in this research is normative juridical research and empirical juridical research.